The prevalence of undernutrition among students attending traditional Ethiopian orthodox Tewahedo church schools in northwest Ethiopia - Shiferaw, Yalelet Fentaw; Asmamaw, Desale Bihonegn; Engidaw, Melaku Tadege; Belay, Daniel Gashaneh; Birhan, Haileyesus; Negash, Wubshet Debebe (Frontiers in Public Health, 2023)
Background: Undernutrition is a major public health concern affecting the health, growth, development and academic performance of school adolescents. During this crucial period, dietary patterns have a vital impact on life time nutritional status and health. The problems of undernutrition among particular groups of traditional school adolescents are not studied. Therefore, this study aimed to assess the prevalence of undernutrition and associated factors among adolescents aged 10-19 years in Orthodox Church School northwest Ethiopia. Methods: An institutional based cross sectional study design was employed from March 1 to 30, 2021. Simple random sampling technique was used to select a total of 848 male traditional school attendants. Data was collected using an interviewer administered semi-structured questionnaire. Nutritional status of study participants was assessed using Anthropometric measurements. WHO Anthroplus software was used for analysis. Both bivariable and multivariable logistic regressions were used to identify the associated factors. The degree of association between the independent and dependent variable was assessed using odds ratio with 95 % confidence interval and p value ≤ 0.05. Result: The prevalence of undernutrition was found to be 61.3% [95% CI: 58.1, 64.6]. Those adolescents who had follow dikuna (AOR=4.3, 95% CI=1.3, 13.6), kinne (AOR=4.5, 95%CI= 1.4, 14.6), aquaqume (AOR=9.9, 95%CI= 2.5, 39.88), tirguame (AOR=6.4, 95%CI=1.6, 25.6), and adolescents whose mothers had no formal education [AOR=3.7, 95%CI: 1.2, 12.8] had higher likelihood of developing undernutrition. Whereas, those adolescents who always wash their hands after a toilet visit [AOR= 0.7, 95%CI: 0.5, 0.98] were less odds of undernutrition as compared with their counterparts. Conclusion: More than three out of five adolescent males were undernourished. Thus, to improve the nutritional status of traditional church school adolescents, extensive health education for the adolescents is essential. Moreover, establishing strong traditional religious school with provision of adequate diversified diet is important. Developing the habit of hand washing after toilet visit and food preparation is also recommended for the adolescent students.